An investigation on the impact of supplier relationshiop management on supply chain performance of pharmaceutical industry. A case study of selected pharmaceutical firms in Zimbabwe - Mandivava, A. (BUSE, 2023)
Recently, there have been reports of pharmaceutical firms facing challenges in their supply chain, a development that has been negatively affecting the lives of many in developing countries like Zimbabwe. Their performance is dwindling and this has been attributed to external pressures most of which are beyond organisational structure and strategy. A substantial part of these pressures can be managed through supplier relationship management hence the purpose of the study was to investigate the impact of supplier relationship management in on supply chain performance of pharmaceutical firms in Zimbabwe. In this study, both theory and empirical testing has revealed the influence supplier relations have on the price of products, quality, lead times and the ability to respond to untimely fluctuations in the supply market. As part of literature review, the theories used in this research study comprise the social exchange theory, Relationship Marketing theory and Systems theory. Moreover, the study employed quantitative research approach and in particular it adopted the explanatory research design. The target population for the research study was 55 officials of the selected pharmaceutical firms. Stratified random sampling technique was used to select the sample size and the sample size was reduced to 48 staff members drawn from 3 departments consisting of Purchasing, Warehousing and Logistics. Sampling units for the study entailed top, middle and lower management comprising of procurement officers, logistic staff and warehouse staff. A questionnaire was used as the main data collection instrument, with a 5 point Likert scale measuring the extent to which the agree or disagree. This was complemented by documentary review. Indeed, more research is therefore recommended on factors such supplier selection, evaluation and supplier development. Pilot study was conducted to test validity and reliability of the questionnaires. Data analysis was done and facilitated by using SPSS software. Reliability was tested using Cronbach alpha 0.7. Data was analysed using both descriptive statistics (frequencies, standard deviation, mean and percentages) and inferential statistics using multiple regression model and correlation. The study used Pearson correlation model to determine the existing relationship between the study variables. The study findings revealed that all study variables (supplier segmentation β=0.270, p<0.05, supplier collaboration β=0.467, p<0.05 and information exchange β=0.247, p<0.05 positively and significantly influence the supply chain performance measurement factors (cost saving, product quality, delivery performance and enhanced flexibility) in the pharmaceutical industry. The study also recommends future studies to incorporate other variables not included in the study. The study also gives room for future studies to be conducted in other Health care institutions
Keywords: Pharmaceutical firms; Supplier relationship management; Procurement